Praktikalitas Media Pembelajaran Android pada Mata Pelajaran Teknologi Jaringan Berbasis Luas: (Studi Kasus Kelas XI TKJ SMKN 8 Padang) - Novita Pramida Sari; Menrisal, Menrisal; Astri Indah Juwita (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to determine the Practicality of Developing Android-Based Learning Media in WAN Broad-Based Network Technology Subjects for Class XI TKJ at SMKN 8 Padang. This study uses research development methods (research & development). The research subjects totaled 36 people. The research model used is the development research model (ADDIE model), with the design development steps as follows. (1) Analyze, (2) design, (3) development, (4) Implementation and (5) Evaluate. The results of the validity test by the experts as a whole the validator test assessment of Android-Based Learning Media in Class XI Class XI WAN-Based Network Technology Subject at SMKN 8 Padang is 87.11%, so the validity level can be interpreted as very valid to use. The results of the practicality test assessment as a whole the practicality assessment of Android-Based Learning Media in Class XI WAN Broad-Based Network Technology Subject at SMKN 8 Padang is 96.12%, so that the level of practicality can be interpreted to be very practical to use. The results of the overall effectiveness test assessment of the effectiveness of Android-Based Learning Media in Class XI WAN Broad-Based Network Technology Subjects at SMKN 8 Padang amounted to 89.22% so that the level of effectiveness can be interpreted to be used very effectively. In conclusion, based on the assessment along with expert input as well as the results of field trials Android-Based Learning Media as a learning medium has been tested for feasibility, superiority, and can be used in the learning process in the Class XI WAN Broad-Based Network Technology subject at SMKN 8 Padang.